1994
DOI: 10.1128/iai.62.6.2395-2403.1994
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of porcine intestinal spirochetes in gnotobiotic pigs

Abstract: Twelve intestinal spirochete strains of porcine origin were characterized on the basis of their phenotypic properties, by multilocus enzyme electrophoresis, and by pathogenicity testing in gnotobiotic pigs. The spirochetes used included two strains of Serpulina hyodysenteriae (B204 and P18A), two strains of Serpulina innocens (B256 and 4/71), one strain from the proposed new genus and species "Anguillina coli" (P43/6/78), and seven non-S. hyodysenteriae strains recently isolated from United Kingdom pig herds w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
32
1
3

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(38 citation statements)
references
References 30 publications
2
32
1
3
Order By: Relevance
“…The disease was referred to as spirochetal diarrhea (25). Diarrhea associated with WBHIS has also been reported by others (6,8,10,20,27,28). Isolation of WBHIS with the capacity to hydrolyze hippurate, but lacking ␤-glucosidase activity, from pigs with diarrhea has been reported (3,5,6), while indole-negative WBHIS with other phenotypes were considered to be nonpathogenic (5,6).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…The disease was referred to as spirochetal diarrhea (25). Diarrhea associated with WBHIS has also been reported by others (6,8,10,20,27,28). Isolation of WBHIS with the capacity to hydrolyze hippurate, but lacking ␤-glucosidase activity, from pigs with diarrhea has been reported (3,5,6), while indole-negative WBHIS with other phenotypes were considered to be nonpathogenic (5,6).…”
supporting
confidence: 74%
“…It was possible to reisolate spirochetes from a suspension of 0.2 g of pig feces in 1 ml of broth which had been inoculated with only 150 spirochetal cells. In a challenge study in gnotobiotic pigs with strains of Serpulina, including S. hyodysenteriae, S. innocens, and strain P43, the number of spirochetes in feces 5 to 10 days postinfection varied from 1 ϫ 10 5 to 2 ϫ 10 9 per g of feces (20), which is equivalent to 2.0 ϫ 10 4 to 4.0 ϫ 10 8 bacterial cells per 0.2 g of feces. The numbers did not differ significantly for pigs with and without clinical signs.…”
Section: Discussionmentioning
confidence: 99%
“…In both cases the presence of normal intestinal flora is required for disease development. 2,10 Both pathologies share similar histological lesions, namely thickening of the epithelium with crypt hyperplasia. 41,42 A previous study showed that CD4 + T cells were diminished in the colonic mucosa of pigs with swine dysentery.…”
Section: Discussionmentioning
confidence: 99%
“…This condition was termed porcine intestinal spirochetosis or spirochetal diarrhea and was characterized by end-on attachment of spirochetes to the colonic epithelium. Subsequently, other researchers have shown an association between colonization of the porcine intestinal tract with certain weakly hemolytic spirochetes and the occurrence of diarrhea (1,6,14,27,30).…”
mentioning
confidence: 99%